Information-based trading in the option market: The predictive power of option-to-stock volume ratio on stock returns : Evidence from the DAX index - Raiskio, Iiris (My University, 2026)
Previous research shows that option trading activity can contain information about future stock returns. In particular, the option-to-stock volume ratio (O/S) has been found to predict stock returns in U.S. markets. This predictive relationship is often explained by the presence of informed traders, who use option markets to act on private information. This study examines whether the O/S ratio predicts future stock returns in a European setting. The analysis focuses on firms included in the DAX index over the period 2020–2025. The empirical analysis is conducted using daily data on option and stock trading volume obtained from the EUREX exchange. The study applies both portfolio sorting and Ordinary Least Squares (OLS) regression to test the predictive power of the O/S ratio. The results do not provide evidence that the O/S ratio predicts future stock returns in the DAX market. Neither the portfolio sorting approach nor the regression analysis shows statistically significant predictive relationships. These findings differ from earlier results reported in U.S. markets. The results suggest that the predictive relationship between option trading activity and stock returns may depend on market-specific characteristics, such as liquidity, trading structure, and investor composition. This thesis contributes to the existing literature by providing evidence from a European market and highlights the importance of institutional context when interpreting the informational role of option trading. Aiempi tutkimus osoittaa, että optiokaupankäynti voi sisältää informaatiota tulevista osaketuotoista. Erityisesti optioiden ja osakkeiden kaupankäyntivolyymin suhteen (O/S) on havaittu ennustavan osaketuottoja Yhdysvaltain markkinoilla. Tätä ennustavuutta selitetään usein sofistikoituneilla sijoittajilla, jotka hyödyntävät yksityistä tietoansa optiomarkkinoilla. Tässä tutkimuksessa tarkastellaan, ennustaako O/S-suhde tulevia osaketuottoja eurooppalaisessa markkinaympäristössä. Analyysi keskittyy DAX-indeksiin kuuluviin yrityksiin ajanjaksolla 2020–2025. Empiirinen analyysi perustuu päivittäiseen optio- ja osakekaupankäyntidataan, joka on saatu EUREX-pörssistä. Tutkimuksessa käytetään sekä portfolioluokittelua että Ordinary Least Squares (OLS) regressioanalyysiä O/S-suhteen ennustekyvyn arvioimiseksi. Tulokset eivät anna näyttöä siitä, että O/S-suhde ennustaisi tulevia osaketuottoja DAXmarkkinalla. Sekä portfolioluokittelu että regressioanalyysi eivät osoita tilastollisesti merkitseviä ennusteyhteyksiä. Tulokset poikkeavat aiemmista Yhdysvaltain markkinoilla tehdyistä tutkimuksista. Tulokset viittaavat siihen, että optiokaupankäynnin ja osaketuottojen välinen ennustava yhteys riippuu markkinakohtaisista tekijöistä, kuten likviditeetistä, markkinarakenteesta ja sijoittajakunnasta. Tämä tutkielma täydentää aiempaa kirjallisuutta tarjoamalla empiiristä näyttöä eurooppalaisesta markkinasta ja korostaa institutionaalisen kontekstin merkitystä optiokaupankäynnin informaatiosisällön tulkinnassa.
Keywords: security market; shares; options (securities); pricing; prices; financial markets; investors; finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance